answersLogoWhite

0


Best Answer

y=-2/3x

User Avatar

Wiki User

โˆ™ 2010-01-20 22:41:55
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards

J's study guide

2 cards

What is the name of Steve on minecraft's name

What is love

โžก๏ธ
See all cards

Steel Tip Darts Out Chart

96 cards

170

169

168

167

โžก๏ธ
See all cards

Add your answer:

Earn +20 pts
Q: -2x plus 3y equals 9
Write your answer...
Submit
Related questions

How do you solve 2x-y equals -6 and 2x plus 3y equals 9?

2x + 3y = 9x = 3, y = 1 therefore 6 + 3 = 9


2x - 3y equals 4 and x plus 4y equals -9?

(-1,-2)


2x plus 3y equals 13 x -y equals 9?

x = 8, y = -1


What is the order pair for 2x - 3y equals 4 and x plus 4y equals -9?

The ordered pair is (-1, -2).


What is the slope of a line that is perpendicular to 6x plus 3y equals -9?

6x+3y = -9 3y = -6x-9 y = -2x-3 Therefore the perpendicular slope is 1/2


What is the y intercept of 2x-3y equals 27?

It is -9


What is the solution of x plus y equals -2 and 2x plus 3y equals -9?

x + y = -2 2x + 3y = -9 You solve this by elimination - multiply both sides of first equation by 3, then subtract, solve for x, then substitute in any of the equations to solve for y 3x + 3y = -6 2x + 3y = -9 subtracting, x = 3 substituting into 1st equation, y = -2-3 = -5


What is 3y equals 4x plus 9 in standard form?

-4x + 3y = 9


1 over 2x plus 13 equals 9?

The answer to 1 over 2x plus 13 equals 9 is x equals -8.


What is the standard form of 3y equals 4x plus 9?

3y = 4x + 9 -4x + 3y = 9 is the standard form


What value of b will make 2x-3y equals 5 and 9y plus bx equals 4 parallel?

2x - 3y = 5 => 3y = 2x - 5 has a gradient of 2/3 9y + bx = 4 => 9y = -bx + 4 has a gradient of -b/9 The two gradiends must be the same if the two lines are parallel: 2/3 = -b/9 so that b = -6


2y plus 3 equals 3y plus 9?

2y + 3 = 3y + 9 2y - 3y = 9 - 3 or -y = 6 so y = -6


2x equals -x plus 9?

2x = -x +9


What is 3y-9 equals 2x in y intercept?

To put the equation 3y - 9 = 2x in y-intercept form (y = mx + b): 3y - 9 = 2x 3y = 2x + 9 (add 9 to both sides of the equation) y = 2/3 x + 3 (divide all terms by 3) The y-intercept is the b term in the equation, which in this example is 3.


What is the solution of 3y plus 9 equals -18?

y= -9


What is the slope of 6x plus 3y equals -9?

Put in function, Y = mX + C, form. 6X + 3Y = - 9 3Y = - 6X - 9 Y = - 2X - 3 -------------------- m(slope) = - 2 ----------------------


What is the inverse function of the equation y equals 4x plus 9 Divided by 2x minus 3?

y = (4x+9)/(2x+3)2xy+3y = 4x+93y-9 = 4x-2xy3y-9 = x(2-2y)x = (3y-9)/(2-2y)So, inverse function is 3x minus 9 divided by 2 minus 27.


What is 4x plus 3y equals 9?

4x + 3y=9 x=0 y=3


Solve the system using any algebraic method a. -5x-y equals -3 ---- x-4y equals 9 b. x plus y-z equals 7 ---- 2x-3y plus z equals 2 ---- 4x plus 2y-2z equals 20?

y=5x+2 if y equals -4


What is the slope of the line that is parallel to 6x plus 3y equals -9?

6x + 3y = -9 So 3y = -6x - 9 or y = -2x - 3 So the slope of the given line is -2 Therefore, the slope a any parallel line is also -2.


5x plus x - 6x plus 2x equals 9?

5x + x - 6x + 2x = 2x


What is the answer for this algebra problem 2x plus 2-2x plus 2 plus 3x-9 equals x plus 9?

x = 7


If 5xequals 9plus 2x then x equals?

If 5 x equals 9 plus 2x then x equals?


What is 6 plus 2x equals 5x plus 9?

6 + 2x = 5x + 9 , 6 - 9 = 5x - 2x , -3 = 3x , x = -1


What is 2x plus 3 equals 9?

if 2x+3=9 then 2x=6 so x=3